Digital logistics as a perspective for the Northern Sea route - Ilin, Igor; Maydanova, Svetlana; Jahn, Carlos; Weigell, Jürgen; Kersten, Wolfgang (epubli, 2021)
Purpose: This paper aims to provide an approach to the digitalization of the Northern Sea Route. Current research and best practices analysis do not contain solutions for such large-scale projects like the digitalization of the Northern Sea Route (NSR). The findings of this paper can help to ensure support for the development of digital services for the NSR. Methodology: The problem is considered in terms of the Enterprise Architecture approach. This study uses The Open Group Architecture Framework (TOGAF), a modern approach to the information systems development, and the Model Based System Engineering (MBSE) method, based on unified models. Findings: Conducted studies suggest that the Northern Sea Route IT-architecture requires a holistic and consistent approach due to the involvement in the process of many different stakeholders. To create a competitive advantage, digital services of the NSR should be implemented on the basis of available best-in-class technologies, and their implementation requires a specific approach, based on the development of reference architecture models and their evaluation. Originality: The Northern Sea Road implementation is a large-scale project and demands a detailed study and thorough elaboration in regard to different aspects. The results of this paper will create a foundation for the modelling of digital services for the NSR which correspond to a modern level of maritime industry development.